2014
DOI: 10.1371/journal.pmed.1001611
|View full text |Cite|
|
Sign up to set email alerts
|

Active or Passive Exposure to Tobacco Smoking and Allergic Rhinitis, Allergic Dermatitis, and Food Allergy in Adults and Children: A Systematic Review and Meta-Analysis

Abstract: In a systematic review and meta-analysis, Bahi Takkouche and colleagues examine the associations between exposure to tobacco smoke and allergic disorders in children and adults. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
3
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 187 publications
5
153
3
8
Order By: Relevance
“…This evidence resumes discussions on gender issues, which still have a huge impact on the health of men and women in terms of decisions, already present in adolescents. A meta-analysis found that active or passive exposure to smoking is associated with an increased risk for allergic pulmonary diseases, and passive smoking is associated with food allergies in children and adolescents (16) . In relation to girls, a study in Finland revealed that smoking interferes with the quality of the production of antibodies in vaccine processes in adolescents, as in the case of the vaccine against the Human Papilloma Virus (HPV) (17) .…”
Section: Discussionmentioning
confidence: 99%
“…This evidence resumes discussions on gender issues, which still have a huge impact on the health of men and women in terms of decisions, already present in adolescents. A meta-analysis found that active or passive exposure to smoking is associated with an increased risk for allergic pulmonary diseases, and passive smoking is associated with food allergies in children and adolescents (16) . In relation to girls, a study in Finland revealed that smoking interferes with the quality of the production of antibodies in vaccine processes in adolescents, as in the case of the vaccine against the Human Papilloma Virus (HPV) (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Air pollutants such as those contained in environmental tobacco smoke present a considerable health problem to the general population, including non-smokers (16,(30)(31)(32). Some studies suggest that active and passive smoking present the risk of IgE sensitisation and atopic conditions, atopic rhinitis and dermatitis in particular (32,33). Our study however found no correlation between passive smoking and elevated IgE in either atopic or non-atopic adolescents, but in atopics passive smoking showed a borderline significant effect on sCD14 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Revisión sistemática: la exposición durante la niñez y la adolescencia se asocia a un mayor riesgo de AA [37]. NE: I SI A…”
Section: Categórica 0= No Fumador Pasivo 1= Fumador Pasivounclassified